2009
DOI: 10.1016/j.healthplace.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Social contacts as a possible mechanism behind the relation between green space and health

Abstract: This study explored whether social contacts are an underlying mechanism behind the relationship between green space and health. We measured social contacts and health in 10,089 residents of the Netherlands and calculated the percentage of green within 1 and a 3km radius around the postal code coordinates for each individual's address. After adjustment for socio-economic and demographic characteristics, less green space in people's living environment coincided with feelings of loneliness and with perceived shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
628
7
35

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 937 publications
(715 citation statements)
references
References 34 publications
45
628
7
35
Order By: Relevance
“…Factors such as deprived and densely populated neighborhoods, social disorganization, and poorquality built environments have shown associations with depression, [175][176][177][178][179] even when neighborhood median income is accounted for. Conversely, higher levels of neighborhood green space in low-income communities have been linked to lower levels of perceived stress and a steeper diurnal decline in cortisol secretion, 180,181 increased social contact, 182 improved mental health, 183,184 and lower all-cause mortality. 185 Although a social drift explanation (ie, people with mental health problems being more likely to move into poor neighborhoods) could at least partially explain some associations between the built environment and negative emotional states or poor mental health, it also has been shown that moving to less disadvantaged neighborhoods appears to decrease psychological distress.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Factors such as deprived and densely populated neighborhoods, social disorganization, and poorquality built environments have shown associations with depression, [175][176][177][178][179] even when neighborhood median income is accounted for. Conversely, higher levels of neighborhood green space in low-income communities have been linked to lower levels of perceived stress and a steeper diurnal decline in cortisol secretion, 180,181 increased social contact, 182 improved mental health, 183,184 and lower all-cause mortality. 185 Although a social drift explanation (ie, people with mental health problems being more likely to move into poor neighborhoods) could at least partially explain some associations between the built environment and negative emotional states or poor mental health, it also has been shown that moving to less disadvantaged neighborhoods appears to decrease psychological distress.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Public urban green space has been shown to facilitate social networking and promote social inclusion in children and adolescents (Seeland et al 2009;Ward Thompson et al 2016). The quantity and the quality of greenery have been linked with improved social cohesion at the neighbourhood scale (de Vries et al 2013) while shortage of green space has been associated with perception of loneliness and lack of social support (Maas et al 2009a). However, the relationships between green space and social well-being are complex.…”
Section: Improved Social Capital and Cohesionmentioning
confidence: 99%
“…92 Green spaces may also affect health by providing spaces for interaction and shared interest, thereby promoting social capital and cohesion. [93][94][95][96] Density of urban tree canopy has been found to be a predictor of social capital. 96 In a public housing setting in Chicago, residents living in areas with green common space reported more use of common space and more social cohesion compared to those living in a barren, ungreen areas.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%